Studi awal masa berbunga dan berbuah Sauromatum horsfieldii Miq. (Araceae) di Pulau Bali - Kurniawan, Agung; Wong, Sin Yeng (Jurnal Biologi Udayana; Vol 26 No 1 (2022): JURNAL BIOLOGI UDAYANA, 2022)
The study of flowering and fruiting periods of Sauromatum horsfieldii Miq. (Araceae) in its natural habitat is the first aroid’s observation on flowering biology which conducted in Bali. This early study aimed to investigate the flowering and fruiting behavior of S. horsfieldii in the natural habitat inside Bali Botanic Garden. The result showed that it took roughly more than 16 days for flowering period, while fruiting time duration completed around 60 days or 2 months. Flowers maturity (anthesis) occured approximately 72 hours or 3 days for a cycle of the flowering time. Female flowers reached anthesis prior to male flowers. Insects were supposed as pollinator which played a significant role to reproduction success. The observation was terminated due to the study’s objects were missing at the same time when the ripening berries had already finished observing. Wild long-tailed macaques and/or wood mice were most likely to be the suspects.